The thyroid gland in postmenopausal women: physiology and diseases - Gietka-Czernel, Małgorzata (Menopause Review/Przegląd Menopauzalny, 2017)
The incidence of most thyroid diseases: hypothyroidism, nodular goitre, and cancer is highest among postmenopausal and elderly women. The diagnosis of thyroid dysfunction in this group of patients is difficult because the symptoms can be nonspecific or common with menopausal and ageing complaints. In the interpretation of thyroid function tests the physiological changes in secretion and metabolism of thyrotropin (TSH) and thyroid hormones must be considered, as well as the influence of comorbidities. Unrecognised thyroid dysfunction leads to increased: cardiovascular risk, bone fractures, cognitive impairment, depression, and mortality. Therapy of thyroid dysfunction is different in postmenopausal and elderly women than in young people; hypothyroidism should be treated with caution, because high doses of L-thyroxine can lead to cardiac arrhythmias and increased bone turnover, and hyperthyroidism should be preferentially treated with radioiodine. Thyroid status beneficially influencing longevity relates to low thyroid function. Thyroid nodules and cancer often affect women over 50 years old; the diagnostic and therapeutic approach is the same as in the general population, but the surgical risk and cancer prognosis is worse than in young patients.